TK BQSR Strategies in Overcoming Challenges of Quranic Online Learning - Nurullah, Nurullah (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Online learning has become a solution for education during the COVID-19 pandemic. Some existing studies consider online learning to provide quality education amidst the pandemic. However, its implementation has caused several problems and challenges for educational institutions, teachers, students, and parents, particularly in early childhood education. This study aims to describe TK BQSR's experience in using the jarimatika quran method for Quran memorization through online learning, identify the challenges, and demonstrate the school's strategies in addressing these challenges. This research adopts a qualitative approach. Data are collected through interviews and documentation and analyzed descriptively. The results indicated that Quran memorization using the jarimatika Quran method at TK BQSR is conducted through WhatsApp, video calls, and YouTube. The challenges encountered in implementing online learning are related to achieving learning targets, teacher proficiency, student interest and motivation, parental support, internet connectivity and data limitations, as well as school facilities and infrastructure. To overcome these challenges, TK BQSR has employed several strategies, including implementing regular evaluation systems, holding focus group discussions among teachers for lesson preparation, conducting weekly tahsin (Quran recitation) sessions for parents, organizing monthly parenting training, providing teacher capacity-building training, availing the services of a learning consultant for the school, and continuous support from the central foundation.